Morbidities among older workers and work exit: the HEAF cohort. (29th July 2022) - Walker-Bone, K; D'Angelo, S; Linaker, C H; Stevens, M J; Ntani, G; Cooper, C; Syddall, H E
Abstract: Background: Governments need people to work to older ages, but the prevalence of chronic disease and comorbidity increases with age and impacts work ability. Aims: To investigate the effects of objective health diagnoses on exit from paid work amongst older workers. Methods: Health and Employment After Fifty (HEAF) is a population cohort of adults aged 50–64 years recruited from English GP practices which contribute to the Clinical Practice Research Datalink (CPRD). Participants have completed questionnaires about health and work at baseline and annually for 2 years: their responses were linked with their objective health diagnoses from the CPRD and data analysed using Cox regression. Results: Of 4888 HEAF participants ever in paid work, 580 (25%) men and 642 (25%) women exited employment, 277 of them mainly or partly for a health reason (health-related job loss (HRJL)). Amongst HEAF participants who remained in work ( n = 3666) or who exited work but not for health reasons ( n = 945), there was a similar prevalence of background health conditions. In men and women, HRJL was associated with inflammatory arthritis, sleep disorders, common mental health conditions and musculoskeletal pain. There were however gender differences: widespread pain and lower limb osteoarthritis were associated with HRJL in women but hypertension and cardiovascular disease in men. Conclusions: Improved diagnosis and management of common conditions might be expected to increase working lives. Workplace well-being interventions targeting obesity and increasing mobility might contribute to extended working lives. Employers of predominantly female, as compared with male workforces may need different strategies to retain older workers. Abstract : Amongst older workers (aged 50–64 years), mental health conditions and painful conditions affecting the musculoskeletal system (bones, muscles, joints) are common causes of work loss. However, amongst men, high blood pressure and heart conditions are an important cause, whereas amongst women, sleep disorders and lower limb osteoarthritis are the main causes. Our findings suggest that employers of predominantly male workers, as compared with female workers, may need different strategies to retain their older workers.